The Relationship between Teachers’ Professional Engagement and Competence in Managing Inclusive Classrooms - Lorna C. Oberes; Lilibeth C. Pinili; Regina E. Sitoy; Reylan G. Capuno; Raymond C. Espina; John V. De Vera; Niña Rozanne T. Delos Reyes; Marjorie B. Añero (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
The study examined teachers’ demographic profile, professional engagement and competence in managing inclusive classrooms, as well as the relationship between these variables at Cebu, Philippines during the school year 2025-2026. There were 30 teachers identified as respondents and were sought out through purposive sampling. Using a descriptive-correlational design, the data were gathered through a survey questionnaire and treated using mean, standard deviation, and Pearson r. The study revealed that most of the teachers had a very strong teaching experience of more than 10 years, leaned towards handling a large class size of 31-40, and had adequate inclusive trainings or seminars attended of more than 10. In terms of professional engagement, teachers perceived themselves as highly engaged in all the dimensions, namely, personalized instruction strategies, communicative scaffolding strategies, collaboration strategies, and assessment strategies. When it comes to teachers’ competence, teachers viewed themselves to have a high proficient competence in the dimensions of noticing diversity and creating a stimulating environment, and highly proficient competence in the dimension of quality of learner interaction. Moreover, it was found out that no significant correlation existed between teachers’ demographic profile and teachers’ professional engagement, and teachers’ demographic profile and teachers’ competence. Conversely, there was a statistically significant correlation between teachers’ professional engagement and competence. It is concluded that professional development needs to be intensified to enhance teachers’ essential skills in implementing inclusive classrooms. Ultimately, the findings became the basis of designing an action plan for the inclusive classroom management.